A variable delay line - Brown, D. C. (College of Aeronautics, 1958)
A variable delay line has been designed and built which can be used as an accurate means of measuring time intervals between 10 and 200 p seconds. The use of such a device for the determination of the temperature coefficient of Youngs Modulus is described.